Jamaica : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Jamaica since 1985. In the early 1990s, Jamaica carried out a number of important structural reforms that had a favorable effect on the public finances, resulting in overall public sector surpluses averaging 3 percent of GDP in FY1993-95. These steps included the elimination of general price subsidies and the decontrol of prices, the elimination of the import monopoly of the Jamaica Commodity Trading Corporation, and the institution of cost pass-through mechanisms for public enterprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet